Research Progress on TCM Syndrome Differentiation of Functional Constipation and Application & Prospect of Factor Analysis - Zhan, Liupeng; Li, Yi (Journal of Contemporary Medical Practice, 2026)
Functional Constipation (FC) is a globally prevalent functional intestinal disorder that severely impairs patients’ quality of life. Modern medicine has not fully clarified its pathogenesis, with limited therapeutic effects and a high risk of drug dependence. Traditional Chinese Medicine (TCM) features holistic regulation and treatment based on syndrome differentiation for FC, yet issues such as non-standardized TCM syndrome diagnosis and inconsistent syndrome classification greatly hinder the promotion and application of TCM. As a multivariate statistical method, factor analysis can effectively reveal the internal structure of complex systems and shows great potential in the standardization and objectification of TCM syndrome research. This paper systematically reviews the research status of FC in modern medicine, the understanding of etiology and pathogenesis as well as research progress on syndrome differentiation of FC in TCM, and the application of factor analysis in TCM syndrome studies. Meanwhile, existing problems in current research and future prospects are analyzed. It aims to provide references for in-depth research on TCM syndromes of FC and promote the standardized development of TCM diagnosis and treatment for this disease.